NOVEL SYNTHESIS AND ANTIMICROBIAL ACTIVITIES OF THIAZINO-OXAZINE DERIVATIVES (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In the designing and synthesis of new heterocyclic compounds, containing two different pharmacophores, we have carried out new series of 3-(4-chlorophenyl)-4-methylidene-4,8-dihydro-2H,5H-1,3-thiazino[5,4-e]-1,3-oxazine-2,5,7(3H)-trione derivatives (5a-5k) in good yields from the cyclization of 5-[(1E)-N- (4-chlorophenyl) ethanimidoyl] -4-hydroxy- 2H-1,3- thiazine-2,6(3H)-dione derivatives (4a-4k) with triphosgene. All the synthesized compounds (5a-5k) were confirmed by spectral analysis. The synthesized compounds (5a-5k) were screened in vitro for their antibacterial activities against S. subtilis (gram positive) and E. coli. (gram negative) while antifungal activity against C. albicans by cup plate method. Some of the products of series were found to have quite good activities as compared to the standard drug streptomycin and flucanozole.